Laparoscopic Salpingectomy: A Simulation-Based Resident as Surgical Teacher (RAST) Program. (October 2016) - York-Best, Carey; Bengtson, Joan; Stagg, Amy
Abstract : BACKGROUND: The ACGME considers resident teaching skills to be a core competency. Simulation is a time efficient way to teach laparoscopic surgical skills. METHODS: An OSTE (Objective Structured Teaching Examination) was devised to evaluate senior resident teaching skills and an OSATS (Objective Structured Assessment of Technical Skills) was devised to evaluate junior resident laparoscopic skills. Resident teacher/learner dyads performed a simulated laparoscopic salpingectomy and were evaluated by a faculty observer. The resident pair also evaluated each other. After didactic teaching the pairs were re-evaluated. Residents were surveyed pre and post the program on their attitudes around surgical teaching. RESULTS: Most residents initially felt comfortable/neutral in their ability to teach surgery and felt neutral that they had received instruction on surgical teaching. Post-workshop residents showed increased confidence in teaching and acknowledged they had received instruction on teaching surgery. Faculty observers noted a 1.3 point increase in the OSTE scores of the senior residents ( P =.006). Junior residents noted a 0.43 point increase in teaching scores ( P =.004). Faculty noted a 0.73 point increase in OSATS score of the junior residents ( P =.004), compared with a 0.35 point increase noted by senior residents ( P =.10). DISCUSSION: The Laparoscopic Salpingectomy Simulation-Based RAST Program provides a time efficient, reproducible means for residents to learn and practice surgical teaching. Residents felt it supplemented previous teaching. Faculty observers noted significant improvement in OSTE scores of senior residents. The smaller improvement noted by the junior residents was largely because they ranked their senior residents highly even on the initial simulation.